Caracterização óptica e magneto-óptica de filmes de GaPN - Oliveira, Polyanna Bruna Alves de (2016)
This project proposes a systematic study of III-V semiconductors, which are promising for integration with silicon. It consists of the characterization of GaPN film samples with different nitrogen concentrations. We investigated the optical and magneto-optical properties of the samples through different experimental techniques, such as: photoluminescence measurements (PL), Magneto-Photoluminescence, Photoluminescence excitation Spectroscopy (PLE), Time-Resolved Photoluminescence Spectroscopy (TRPL) and Raman Spectroscopy. This study is the result of a parternship between the Federal University of São Carlos, Universidade Estadual de Campinas and the National Institute of Applied Sciences in Rennes, France.